Development of GAVIAMORIDA E-Booklet based on Diversity of Gastropods and Bivalves Research at Mangrove Morosari Demak as Alternative Source of Learni - Romadhoni, Mar`atush Sholihah; Widiyaningrum, Priyantini; Susanti, R. (Universitas Negeri Semarang)
The Mangrove Morosari Demak was once a densely populated area, but due to the abrasion process of the Java Sea, the area was eventually submerged. This condition affects the survival of Gastropods and Bivalves. This study aims to develop an e-booklet based on the research of Gastropods and BivalvesÃ¢â‚¬â„¢ Diversity in the Mangrove Morosari Demak. The e-booklet is named GAVIAMORIDA which stands for Gastropods and Bivalves in the Mangrove Morosari Demak. This development research uses the ADDIE method with 5 stages: Alanyze, Design, Develop, Implement and Evaluate. This research resulted a kind of e-booklet Ã¢â‚¬Å“GAVIAMORIDAÃ¢â‚¬Â with detailed information about 11 types of Gastropods and 1 Bivalves which found in the Mangrove Morosari Demak. The average value of diversity index (H ') is 2.116 (moderate), evenness index (E) is 0.912 (high), and dominance index (C) is 0.131 (stable). The results of the validation from two kinds validators (experts and users) were 85.61% which were classified as